Azolla microphylla Kaulf. (Salviniaceae): A new pteridophytic record for Bangladesh - Alfasane, Md. Almujaddade; Bhuiyan, Rauf Ahmed; Jolly, Jesmin Akhter; Islam, Shahima (Bangladesh Journal of Plant Taxonomy, 2019)
Not available.